Interferon-α, but not the ABL-kinase inhibitor imatinib (STI571), induces expression of myeloblastin and a specific T-cell response in chronic myeloid leukemia - Burchert, Andreas; Wölfl, Stefan; Schmidt, Manuel; Brendel, Cornelia; Denecke, Barbara; Cai, Dali; Odyvanova, Larissa; Lahaye, Tanja; Müller, Martin Christian; Berg, Thomas; Gschaidmeier, Harald; Wittig, Burghardt; et al. (Blood, 2003)
Chronic myeloid leukemia (CML) is a clonal disease of hematopoietic stem cells caused by a reciprocal translocation of the long arms of chromosomes 9 and 22. In human leukocyte antigen A*0201+ (HLA-A*0201+) individuals, response after interferon-α (IFN-α) was shown to be associated with the emergence of CML-specific cytotoxic T cells that recognize PR-1, a myeloblastin (MBN)-derived nonapeptide. In contrast, imatinib potently induces remissions from CML by specific inhibition of the ABL tyrosine kinase. Here, we explored molecular regulations associated with CML responses under different treatment forms using cDNA-array. Expression of MBN was found to be down-regulated in remission under imatinib therapy (0 of 7MBN+ patients). In contrast, MBNtranscription was readily detectable in the peripheral blood in 8 of 8 tested IFN-α patients in complete remission (P = .0002). IFN-α-dependent MBNtranscription was confirmed in vitro by stimulation of peripheral blood mononuclear cells (PBMCs) with IFN-α and by IFN-α-mediated activation of the MBN promoter in reporter gene assays. Finally, with the use of HLA-A*0201-restricted,MBN-specific tetrameric complexes, it was demonstrated that all of 4 IFN-α-treated patients (100%), but only 2 of 11 imatinib patients (19%), in complete hematological or cytogenetic remission developed MBN-specific cytotoxic T cells (P = .011). Together, the induction of MBNexpression by IFN-α, but not imatinib, may contribute to the specific ability of IFN-α to induce an MBN-specific T-cell response in CML patients. This also implies that the character of remissions achieved with either drug may not be equivalent and therefore a therapy modality combining IFN-α and imatinib may be most effective.
Gesehen am 13.05.2022